Dynamic metabolic changes after permanent cerebral ischemia in rats with/without post-stroke exercise: a positron emission tomography (PET) study. (May 2014) - Jiang, Xiao-Feng; Zhang, Tong; Sy, Christopher; Nie, Bin-Bin; Hu, Xue-Yan; Ding, Yuchuan
Abstract : Objectives: Recent studies have suggested that rehabilitation therapy can accelerate functional recovery after a stroke. Although often overlooked, the cortical hemisphere contralateral to an infarction plays an important role. This study investigates alterations in metabolism of both the damaged ('ipsilateral') as well as the undamaged ('contralateral') hemisphere using 18 F-fluorodeoxyglucose (FDG)-micro-positron emission tomography (PET) in a rat permanent stroke model (with or without post-injury exercise) in order to elucidate the relative importance of either hemisphere to the recovery process following stroke. Methods: Thirty-six adult, male Sprague-Dawley rats were divided into four groups before subsequent surgery: sham controls with or without exercise, and ischemic ('stroke') groups with or without exercise. Fluorodeoxyglucose micro-PET imaging was performed at 7, 14, and 21 days after the designated procedure according to group assignment. The imaging data was analyzed by ANOVA using SPMratIHEP software. Results: Both exercise and ischemia have measurable effects on the motor cortex as well as on the striatum, the effects of which notably include the contralateral hemisphere. To that end, regions of the contralateral motor cortex and striatum have been found to be in a hypermetabolic state following exercise. We further observed that exercise reversed the hypometabolism caused by ischemia back to control levels from day 7 through day 21 on the ipsilateral side. Its effect on the contralateral hemisphere, notably, bolsters an already vigorous response observed after ischemic insult. Thus, the beneficial effect of exercise, as inferred by an increase in metabolic activity, is evident in both hemispheres. Discussion: These findings suggest that the contralateral hemisphere can compensate for the damaged cortex by remodeling neuronal activity. Thus, clinical treatments specifically targeted to the 'intact' hemisphere following stroke may provide a complimentary strategy for promoting recovery of functional deficits and for improving quality of life in stroke patients.